Teacher and Elementary School Students Perceptions of Online Learning Methods - Wasti Sanda; Priska Efriani Luansi Ero; Mas’ud Mas’ud (Edumaspul: Jurnal Pendidikan, 2024)
The objective of this research is to investigate and understand the perspectives of teachers and students regarding the experience of online learning implemented during the Covid-19 pandemic in class VIA at SDN 199 Mappa. This study adopts a qualitative approach, specifically utilizing a case study design. The primary respondents include teachers and students from higher classes (IV, V, and VI). Data were collected through interview methods, while data validity was analyzed through triangulation techniques. The research findings indicate that teachers and students at SDN 199 Mappa express their understanding of the concept of online learning. Some applications utilized include Google Form and WhatsApp. However, both parties also express the view that online learning is less effective due to constraints in facilities and infrastructure, especially internet network disruptions during the implementation of online learning. Furthermore, the learning process is considered to impose limitations on teachers in monitoring student progress.